The effect of Pilates on patients’ chronic low back pain. A pilot study. - MacIntyre, Leanne (My University, 2006)
The Pilates exercise method applies many of the principles of lumbar stabilisation that have been found to be effective in the treatment of chronic low back pain. Pilates has recently found its way into the physiotherapy setting, where it is being integrated into the rehabilitation of patients with low back pain. This study consisted of a randomised control trial using an intervention group that underwent a twelve-week Pilates programme, and control group that continued with standardised physiotherapy treatment as necessary. Baseline, three-week, and twelve-week scores for a Visual Analogue Scale for pain and the Roland Morris Disability Questionnaire were recorded and compared. The Pilates group showed significantly greater improvements in pain and functional disability mean scores when compared to the control group (p=0.059 and p=0.026 respectively). It therefore appears that Pilates can be recommended as an effective treatment modality for the reduction of pain and the improvement of functional disability for chronic low back pain sufferers.
Faculty of Health Sciences School of Therapectic Sciences 0213128j 0117899331
Keywords: Pilates; chronic; pain; low back; exercise